2018
DOI: 10.3389/fpsyg.2018.00998
|View full text |Cite
|
Sign up to set email alerts
|

Are Manipulation Checks Necessary?

Abstract: Researchers are concerned about whether manipulations have the intended effects. Many journals and reviewers view manipulation checks favorably, and they are widely reported in prestigious journals. However, the prototypical manipulation check is a verbal (rather than behavioral) measure that always appears at the same point in the procedure (rather than its order being varied to assess order effects). Embedding such manipulation checks within an experiment comes with problems. While we conceptualize manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
211
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(237 citation statements)
references
References 52 publications
5
211
0
4
Order By: Relevance
“…This procedure is well established and allows fully controlled laboratory studies (e.g., Hafenbrack et al, 2014;Kiken & Shook, 2011;Long & Christian, 2015;Schofield, Creswell, & Denson, 2015). Thus, it can be concluded that brief mindfulness exercises can increase state mindfulness compared to various control groups (for an overview of manipulation check problems, see Hauser, Ellsworth, & Gonzalez, 2018). Notably, in contrast to the four remaining studies, in this study, we included a no-treatment control condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure is well established and allows fully controlled laboratory studies (e.g., Hafenbrack et al, 2014;Kiken & Shook, 2011;Long & Christian, 2015;Schofield, Creswell, & Denson, 2015). Thus, it can be concluded that brief mindfulness exercises can increase state mindfulness compared to various control groups (for an overview of manipulation check problems, see Hauser, Ellsworth, & Gonzalez, 2018). Notably, in contrast to the four remaining studies, in this study, we included a no-treatment control condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, Lueke and Gibson (2016) found that state mindfulness was increased after a 10-min mindfulness exercise (become aware of sensations in the body, such as breathing) compared to a pure control condition (listening to an audiotape describing an English countryside), as well as to an attention condition (paying attention to the word "parish" while listening to the audiotape of the pure control condition). Thus, it can be concluded that brief mindfulness exercises can increase state mindfulness compared to various control groups (for an overview of manipulation check problems, see Hauser, Ellsworth, & Gonzalez, 2018). Given that mindfulness intervention exercises can at first feel challenging for inexperienced people (Creswell, 2017), future research should apply extended mindfulness trainings.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that only those participants that passed the IMC were affected by the treatment. Because explicit manipulation checks can amplify, undo, or interact with the effects of a treatment, recent research suggests non-intrusive behavioral checks of attention 44 . We follow this method in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…In short, essentially the same methodological and statistical considerations that apply to the validation of measurements also apply to the validation of manipulations. However, although there is a long tradition of thorough validation research and theory for measurements (Cronbach & Meehl, 1955;Loevinger, 1957;Nunnally, 1970;Raykov & Marcoulides, 2011), the empirical validation of experimental treatments in social psychology has been dominated by simpler techniques collectively known as manipulation checks (Sigall & Mills, 1998;Hauser et al, 2018).…”
Section: Construct Validationmentioning
confidence: 99%
“…Correlates: Indirect manipulation checks. Sometimes, however, it is not possible to directly measure the construct of interest, or there may be serious concerns that a direct measure could render a manipulation ineffective if it alerts participants to the purpose of the manipulation (Hauser, Ellsworth, & Gonzalez, 2018;Mills, 1969). It can also be useful to measure related constructs in order to provide convergent validity evidence (Cronbach & Meehl, 1955).…”
Section: Independent Variable Measures: (Direct) Manipulation Checksmentioning
confidence: 99%